“Even if the baby is missing his head, there can be no abortion” - Motta Ochoa, Angelica (2019)
This study examines the obstacles to access therapeutic abortion (TA) based on the description and analysis of the crucial moments in the critical path followed by five Peruvian women trying to gain access to the procedure. The cases hereafter mentioned show the strong opposition by part of the health system in providing access to TA. Even when prevailing law exist since 1924, ratified in 1991, and an approved protocol since 2014. The path taken by the women who participated in this study proves control over women’s bodies through the mandate of motherhood, when the product of conception is not expected to survive, to be fundamental to the process of structural violence in the system.